2020
DOI: 10.1101/2020.05.07.082750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust decomposition of cell type mixtures in spatial transcriptomics

Abstract: Spatial transcriptomic technologies measure gene expression at increasing spatial resolution, approaching individual cells. However, a limitation of current technologies is that spatial measurements may contain contributions from multiple cells, hindering the discovery of cell type-specific spatial patterns of localization and expression. Here, we develop Robust Cell Type Decomposition (RCTD, https://github.com/dmcable/RCTD), a computational method that leverages cell type profiles learned from single-cell RNA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…Moreover, cell2location revealed that 50% of Slide-Seq "beads" (i.e. 10-micron diameter spatial locations) contained more than 1 cell type ( Fig S10B), consistent with the previous observations 4 .…”
Section: Cell2location Accurately Maps Mouse Brain Cell Typessupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, cell2location revealed that 50% of Slide-Seq "beads" (i.e. 10-micron diameter spatial locations) contained more than 1 cell type ( Fig S10B), consistent with the previous observations 4 .…”
Section: Cell2location Accurately Maps Mouse Brain Cell Typessupporting
confidence: 90%
“…Emerging spatial genomics technologies hold considerable promise for characterising tissue architecture, providing key opportunities to map resident cell types and cell signalling in situ, thereby helping guide in vitro tissue engineering efforts. Despite existing proof of concept applications [1][2][3][4][5] , it remains a challenge to define versatile and broadly applicable spatial genomics technologies and workflows. One reason is the enormous variation in tissue architecture across organs, ranging from the brain with hundreds of cell types found across discrete anatomical regions to immune organs with continuous cellular gradients and dynamically modified microenvironments.…”
Section: Introductionmentioning
confidence: 99%
“…5 and 6A, Supplementary Notes). We also compared it with RCTD 30 , which is a newly developed method for deconvolution. RCTD also performed well (median AUC value of 0.95, Supplementary Fig 5. and 6A), but it was considerably slower than the other methods ( Supplementary Fig.…”
Section: Analysis Of Data With Lower Spatial Resolutionmentioning
confidence: 99%
“…The spatial arrangement of cells is key to understanding a morphologically complex tissue such as the endometrium, where a cell's function may differ depending on signals it receives from neighbouring cells (16). Many spatiallyresolved transcriptomics methods are not quite at single-cell resolution, and rely on the computational integration of coupled single-cell (or single nuclei) transcriptomes to achieve this level of detail (17)(18)(19). These genomic technologies are the basis of the Human Cell Atlas initiative, which aims to map all cells in the human body (20).…”
mentioning
confidence: 99%